2016
DOI: 10.1007/s10661-016-5177-7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical power to detect change in a mangrove shoreline fish community adjacent to a nuclear power plant

Abstract: An expansion is underway of a nuclear power plant on the shoreline of Biscayne Bay, Florida, USA. While the precise effects of its construction and operation are unknown, impacts on surrounding marine habitats and biota are considered by experts to be likely. The objective of the present study was to determine the adequacy of an ongoing monitoring survey of fish communities associated with mangrove habitats directly adjacent to the power plant to detect fish community changes, should they occur, at three spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Assessing the temperature tolerance range of aquatic organisms is of great guiding significance for the construction of nuclear power plants and other human activities [7]. Numerous studies have reported the temperature tolerance ranges of various aquatic organisms, especially animals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing the temperature tolerance range of aquatic organisms is of great guiding significance for the construction of nuclear power plants and other human activities [7]. Numerous studies have reported the temperature tolerance ranges of various aquatic organisms, especially animals [8][9][10].…”
Section: Introductionmentioning
confidence: 99%